PENERAPAN STRATEGI PEMASARAN PRODUK HASIL PERIKANAN UMKM DESAKITARA BERBASIS ONLINE - Heni Irawati; Luthfiyana, Novi; Bija, Stephanie (LPPM IST AKPRIND Yogyakarta, 2022)
Karaca crab is one of the processed fishery products from Desakitara UMKM, located in Juata Permai Village, Tarakan City. The processed products of keraca crab have the potential for nutritional and economic value. However, the application of marketing strategies carried out by Desakitara SMEs has not been optimal, so their distribution is still limited and not well known to the public. This activity aims to provide marketing assistance for fishery products to MSME Desakitara Tarakan City through community service programs. The activity method starts from the preparation, socialization, mentoring, and monitoring and evaluation stages. The results of the activities that have been carried out are increasing partner knowledge and technology related to online-based marketing, increasing partner skills and creativity in marketing by applying the 4P principles: product (product in the form of goods/services), price (price), promotion (promotion) and place, as well as increasing sales and income of Desakitara MSME partners. After the activity has been carried out, Desakitara MSMEs are now productive again. There is an increase in income to support the development of the potential of tropical marine resources. Keywords: crustacean crab, promotion, savory crabs